Source Apportionment and Concentration of Potentially Toxic Elements in Surface Water and Sediments of Okulu-Aleto River, Rivers State, Nigeria - Omobolaji O. Afolabi; A. I. Hart; H. O. Nwankwoala (Ecotoxicology and Environmental Health, 2026)
Urbanization and industrial activities continuously introduce potentially toxic elements (PTEs) into the terrestrial and aquatic environments, leading to various health-related challenges. This study evaluates the concentration of PTEs (Cadmium (Cd), Chromium (Cr), Copper (Cu), Nickel (Ni), Zinc (Zn), Lead (Pb) and Iron (Fe)) and sources identification in the surface water and sediment of Okulu-Aleto River, Rivers State, Nigeria. Using the Atomic Absorption Spectroscopic technique, the concentration of the studied PTEs were monitored for 4 surface water and 3 sediment samples. The mean concentration showed that the PTEs descended as Pb (0.126) > Cr (0.122) > Ni (0.061) > Cu (0.051) > Zn (0.039) > Cd (0.005) and all concentrations are within the WHO limit for surface water. The mean concentration descended as Cu (1.482) > Zn (1.215) > Cr (0.265) > Pb (0.119) > Ni ≥ Cd and all concentration are within the WHO limit except Cr across all sampling points and Cu at the upstream sampling point. Multivariate statistical analyses, including Pearson Correlation Coefficient and Principal Component Analysis, identified both lithogenic and anthropogenic sources, with industrial discharges, wastewater inputs, and sand mining activities contributing significantly to contamination. Strong positive loadings of Cr, Cu, Ni, and Pb indicated shared anthropogenic origins, while variations in Fe and Zn suggested mixed sources. Continuous monitoring and integrated pollution management strategies are therefore recommended to safeguard ecosystem integrity and public health.